EFFECT OF GROSS PROFIT, OPERATING PROFIT, NET PROFIT AND RECEIVABLES IN PREDICTING FUTURE OPERATING CASH FLOWS - Siti Aisyah Nasution; Robintan Tamba; Mira Mawarani Br. Sihombing; Nurwani Nurwani (Jurnal Ipteks Terapan, 2023)
This study aims to analyze the effect of gross profit, operating profit, net profit and accounts receivable in predicting future operating cash flows partially and simultaneously. This research was carried out in the Food and Beverage sub-sector which is listed on the Indonesia Stock Exchange in 2017-2021. The sample was determined based on the purposive sampling method, with a total sample of 13 companies in the food and beverage sub-sector, so that the total observations of this study were 65 observations. The data used in this research is secondary data. The data collection method uses documentation through the official IDXu website www.idx.co.id. The results of the study of gross profit and operating profit partially show that gross profit and operating profit have a positive and significant effect on predicting operating cash flow in the future. Meanwhile, Net Profit and Receivables partially show that Net Profit and Receivables have a negative but significant effect in predicting future Operating Cash Flows. The results of the research are Gross Profit, Operating Profit, Net Profit and Receivables simultaneously have a significant and positive effect in predicting future Operating Cash Flows.